Comparison of Accelerated Life Tests for Two Different Systems Generated Using the Arrhenius Model - Shim, Kyubark (International Journal of Membrane Science and Technology, 2023)
Accelerated testing consists of a variety of methods aimed at shortening the life of a product or hastening its performance degradation in a short period of time. The purpose of these tests is to quickly obtain data that, when properly modeled and analyzed, can provide the desired information about a product’s lifetime or performance under normal use. Accelerated life testing will subject a product to conditions that exceed normal service parameters in order to uncover defects and potential failure modes. Since the guidelines for statistical analysis of thermal life test data in accelerated life tests (ANSI/IEEE Std. 101-1987) were enacted, they have been used to analyze the results of many experiments. However, Shim (2004) only used a small amount of data obtained from a limited environment for analysis of ANSI/IEEE Std. 101-1987 results, so simulations were conducted using previous research results to supplement the accuracy of the analysis. In this paper, two different systems or materials generated using the Arrhenius equation are compared in an accelerated life test to estimate the correct lifetime.